The Influence Of Job Involvement And Perceived Organizational Support On Job Satisfaction Of Civil Servant At The Department Of Transportation, Kubu Raya Regency - Ranti Nada Permaisella; Arninda Arninda (UNIVED Press, 2025)
This study aims to determine the effect between job involvement, perceived organizational support on job satisfaction. With 45 respondents, using a quantitative approach. The analysis used to examine the data includes instrument test, validity test, reliability test, classical assumption test, normality test, linearity test, multicollinearity test, multiple linear regression analysis, coefficient of determination, simultaneous F test, and partial t test. Based on the analysis, it can be concluded that the correlation coefficient (R) obtained is 0.626 which indicates that between job involvement, perceived organizational support and job satisfaction have a strong relationship. Simultaneous F test shows that job involvement and perceived organizational support simultaneously have a significant influence on job satisfaction.Partial t test shows that the perceived organizational support variable partially affects job satisfaction.